Differences in confidence in public institutions across generations of Canadians - Christoph Schimmele; Max Stick; Maciej Karpinski; Amélie Arsenault (Economic and Social Reports)
Using data from the 2020 General Social Survey, this study provides insights on generational differences in confidence in the police, the justice system and courts, the federal Parliament, and the Canadian media. While immigrants who came to Canada in adulthood had higher levels of confidence in these institutions than Canadians of the third generation or more, those who immigrated during childhood had similar or lower levels of confidence. These age-at-arrival patterns among immigrants were largely consistent across racialized groups. Overall, second-generation Canadians had lower levels of confidence in the police, the justice system and courts, and the Canadian media than Canadians of the third generation or more.